Women, Power, and Religious Patronage in the Middle Ages - Jordan, Erin L. author.
VIII, 193 p.
Keywords: By examining a significant corpus of secular and monastic charters, this study provides a more complex understanding of the role of religious patronage in medieval society, specifically offering a glimpse of the experience of female rulers in a period when actions were often constrained and obscured by gender bias.